Are Clients Being Improperly Denied Coverage for an Eating Disorder When in a Residential Treatment Center?. (3rd April 2021) - Zucker, Temimah; Pollack, Daniel
ABSTRACT: Individuals struggling with eating disorder diagnoses purse higher levels of care to treat the medical, behavioral, and psychiatric aspects of their disorders. The criteria for coverage at a higher level of care often overlooks the holistic nature of treatment required for long-lasting recovery. The following piece will explore clinical information related to the true nature of an eating disorder, criteria for insurance coverage, and specific cases that show denials of care and the implication for clients seeking out support as well as an outline of necessary changes.